Plasma Derived from Human Umbilical Cord Blood Modulates Mitogen-Induced Proliferation of Mononuclear Cells Isolated from the Peripheral Blood of ALS Patients - David J. Eve; Jared Ehrhart; Theresa Zesiewicz; Israt Jahan; Nicole Kuzmin-Nichols; Cyndy Davis Sanberg; Clifton Gooch; Paul R. Sanberg; Svitlana Garbuzova-Davis Ph.D., D.Sc. (Cell Transplantation, 2016)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by degeneration of motor neurons in the spinal cord and brain. This disease clinically manifests as gradual muscular weakness and atrophy leading to paralysis and death by respiratory failure. While multiple interdependent factors may contribute to the pathogenesis of ALS, increasing evidence shows the possible presence of autoimmune mechanisms that promote disease progression. The potential use of plasma derived from human umbilical cord blood (hUCB) as a therapeutic tool is currently in its infancy. The hUCB plasma is rich in cytokines and growth factors that are required for growth and survival of cells during hematopoiesis. In this study, we investigated the effects of hUCB plasma on the mitogen-induced proliferation of mononuclear cells (MNCs) isolated from the peripheral blood of ALS patients and apoptotic activity by detection of caspase 3/7 expression of the isolated MNCs in vitro. Three distinct responses to phytohemagglutinin (PHA)-induced proliferation of MNCs were observed, which were independent of age, disease duration, and the ALS rating scale: Group I responded normally to PHA, Group II showed no response to PHA, while Group III showed a hyperactive response to PHA. hUCB plasma attenuated the hyperactive response (Group III) and potentiated the normal response in Group I ALS patients, but did not alter that of the nonresponders to PHA (Group II). The elevated activity of caspase 3/7 observed in the MNCs from ALS patients was significantly reduced by hUCB plasma treatment. Thus, study results showing different cell responses to mitogen suggest alteration in lymphocyte functionality in ALS patients that may be a sign of immune deficiency in the nonresponders and autoimmunity alterations in the hyperactive responders. The ability of hUCB plasma to modulate the mitogen cell response and reduce caspase activity suggests that the use of hUCB plasma alone, or with stem cells, may prove useful as a therapeutic in ALS patients.